"We're potentially worsening health inequalities": Evaluating how delivery of the 2022 London polio booster campaign was tailored to Orthodox Jewish families to reduce transmission vulnerability - Ben Kasstan; Sandra Mounier-Jack; Ana Zuriaga-Alvaro; Leonora G. Weil; Tracey Chantler (Elsevier, 2023)
A polio booster campaign targeting all children aged 1-9 was implemented across London between August-December 2022 as part of a national enhanced poliovirus incident response. Orthodox Jewish (OJ) children were particularly vulnerable to transmission due to disparities in childhood vaccination coverage and the transnational spread of poliovirus affecting linked populations in New York and Israel. This study aimed to evaluate how the polio booster campaign was tailored to increase uptake and enable access for OJ families in northeast and north central London boroughs, and the impact of the campaign on local-level vaccine inequities. Semi-structured in-depth interviews (n = 36) were conducted with participants involved in the implementation and delivery of the polio booster campaign, and OJ mothers. Site visits (n = 5) were conducted at vaccine clinics, and rapid interviews (n = 26) were held to explore parental perceptions of the poliovirus incident and childhood immunisations. Enablers to vaccination during the campaign included the production of targeted printed communications and offering flexible clinic times in primary care settings or complementary delivery pathways embedded in family-friendly spaces. Barriers included digital booking systems. Mothers reported being aware of the poliovirus incident, but the majority of those interviewed did not feel their children were at risk of contracting polio. Healthcare provider participants raised concerns that the vaccine response had limited impact on reducing disparities in vaccine uptake. While OJ families were recognised as a priority for public health engagement during the poliovirus incident response, this evaluation identified limitations in reducing transmission vulnerability during the booster campaign. Lessons for future campaign delivery include effectively conveying transmission risk and the urgency to vaccinate. Priorities for mitigating vaccine inequities include public engagement to develop messaging strategies and strengthening the capacity of primary care and complementary delivery pathways to serve families with higher-than-average numbers of children.